NEW HIRING SYSTEM AT PT SINAR TIRTA BUANA - Yulia Shinta Putri; Irfan Irfan, Skom.,MMSI (Jurnal Sistem Informasi, 1998)
Running system at PT Tirta Buana Sianr data processing was still manually so that it requires precision and a long time to process all that is necessary to reduce the working efficiency of civil service recruitment process so that in addressing these problems can be computerized as in data processing can be done automatically. Implementation of recruitment processes in PT Sinar Tirta Buana implemented carefully to obtain high quality human resources to support the company's productivity. number of applications coming into the company caused the company be more selective in choosing prospective workers (employees), and for prospective workers (employees) that cause a sense of competitiveness among prospective workers (employees).